2010
DOI: 10.1016/j.juro.2010.06.116
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate Presentation of High Risk Prostate Cancer in a Safety Net Health System

Abstract: Purpose: Most prostate cancer research is based on relatively homogenous cohorts of men, often with comparatively high socioeconomic status. We describe prostate cancer characteristics in men treated in a public health system and hypothesize a disproportionate burden of high risk disease in this population. Materials and Methods:We created a clinical registry from a review of the medical records of 377 men diagnosed with prostate cancer in the San Francisco General Hospital system, which provides care to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
1
9
1
Order By: Relevance
“…Potential HCC knowledge gaps among providers may include misconceptions about screening and treatment guidelines for HCC . At the patient level, individuals at SNHs often undergo less preventive care, have advanced medical comorbidity, and have notable nonmedical social barriers to care . Previous studies have also suggested differential levels of knowledge about HCC between SNHs and non‐SNHs .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Potential HCC knowledge gaps among providers may include misconceptions about screening and treatment guidelines for HCC . At the patient level, individuals at SNHs often undergo less preventive care, have advanced medical comorbidity, and have notable nonmedical social barriers to care . Previous studies have also suggested differential levels of knowledge about HCC between SNHs and non‐SNHs .…”
Section: Discussioncontrasting
confidence: 55%
“…[26][27][28][29] At the patient level, individuals at SNHs often undergo less preventive care, have advanced medical comorbidity, and have notable nonmedical social barriers to care. 10,30,31 Previous studies have also suggested differential levels of knowledge about HCC between SNHs and non-SNHs. 32,33 Although we did not find differences in treatment and overall survival by safety net designation in a conditional landmark analysis accounting for patient comorbidity and liver function, these findings highlight the importance of large multicenter studies using clinically granular data to explore reasons for differences in treatment and outcomes between SNHs and non-SNHs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented disparities in the presentation of advance or mPCa based on presentation to a government-funded vs. private hospital [7], low income and lack of insurance [5,6], and nonwhite race [5,8]. Given the large scale of the NCDB, we were able to simultaneously account for SES, race, and insurance in our cohort which revealed that each variable independently affected the odds of presenting with mPCa.…”
Section: Discussionmentioning
confidence: 92%
“…19 Furthermore, analyses of different disadvantaged patient cohorts in the US showed disproportionately high CaP severity relative to the rest of the US population. 20, 21 In the current study, we attempted to distinguish between disease biology and surgical technique by adjusting for aggressive disease characteristics, including pathologic Gleason sum, ECE, and SVI, in our multivariate models. While we still found lower SES patients to have higher odds of PSM, suggesting technique explained at least some of the excess PSM among men with lower SES, ultimately, whether the higher risk of PSM is due to surgeon-level or disease-specific factors remains to be determined.…”
Section: Discussionmentioning
confidence: 99%